Lateral field excitation properties of langasite single crystal - 马廷锋 张超 冯冠平 江小宁 (Chinese physics B, 2010)
In this work, bulk acoustic wave propagation properties of langasite single crystal excited by lateral electric field have been investigated. Three important crystal cuts have been identified for different operational modes of lateral field excitation （LFE） on langasite substrate, namely the （yxl）65° （pure-LFE mode）, （yxl）45° （quasi-LFE mode）, and （yxl）0° （pseudo-LFE mode）. Devices on langasite substrate with the above cuts were fabricated and tested, and the experimental results agree well with the theoretical analysis. It is found that a pure thickness shear mode exists in the （yxl）65° langasite LFE device with the bare side facing liquid, and no spurious mode is found due to its moderately large piezoelectric coupling factor. In addition, （yxl）0° langasite LFE device is also found suitable for liquid phase sensing applications.